Aquaculture and Horticulture Programs: Impacts of Single vs. Multiple Interventions in Bangladesh. - Webb, Patrick. (Tufts University. Tisch Library., 2017)
This presentation was given to the Technical Advisory Group as an update on the Nutrition Innovation Lab's ongoing interventions in Bangladesh, and the preliminary findings.; Keywords: Bangladesh, updates, TAG, technology interventions, aquaculture, horticulture, Tufts University.; NIL Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy